History as rhetoric : style, narrative, and persuasion - Carpenter, Ronald H., 1933- (Studies in rhetoric/communication., 1995)
In the realm of the written word, Ronald Carpenter reserves a privileged place for historical writing. He contends that because of its assumed credibility, historical writing holds sway over the present attitudes and future actions of the general public and world leaders. Through extensive primary-source research into the public and private writings of such well-known and widely read American historians as Frederick Jackson Turner, Alfred Thayer Mahan, and Allan Nevins, Carpenter examines what happens to this inherently credible medium when rhetorical prowess helps shape the writing of history. He also evaluates the power that such discourse exercises on the public at large and on individuals empowered with making public policy.